Patterns of Hospital Ownership and Control - Hamilton, James A. (Book collections on Project MUSE., 1961)
Based on a study of data about nearly 7,000 independent unites of hospital service in the United States, this book classifies and describes the patterns or types of hospital ownership and control to be found in the hospital industry. For each pattern, information is given on the organizational structure and governing authority, history, significance, finances, educational activities, administration, medical staff, groups or associations within the pattern, and future trends. The book will enable students of hospital administration to get an overall view of the hospital industry and a familiari.